Student experiences in a university preparatory programming course - Spikol, Daniel; Dybdal, Martin; Elmeskov, Dorte C. (Frontiers in Computer Science, 2022)
Even though computer science is currently being integrated into primary and secondary education worldwide, we cannot yet make assumptions about our student's prior knowledge of computing. Every student might have different conceptions about the field of study they are about to enter. Students start at computer science programs with different prior experiences with programming, ranging from no experience to a high degree of proficiency. At the Department of Computer Science, University of BLINDED, we have designed a two-week voluntary summer kickstart course in programming to help students in this transition into our three computer science programs. To evaluate the course, we followed three groups of students. Group one with no/limited programming experience attended the kickstart course. The second group with no/little programming experience did not participate in the course, and the third group of students with programming experience did not participate in the class. We observed the kickstart course and conducted interviews. We followed up about three weeks after the start of the semester and then again at the end of the semester in December. Our findings suggest that the course reduces the gap in programming experiences and strengthens students' self-efficacy and sense of belonging. However, the approach creates a social gap between students who have not attended the course with no/limited experience at the beginning of the semester. Even though the students in December do not experience any difference between students who have attended the course and those who have not, it is important to consider this social gap at the beginning of the semester when designing and planning a preparatory course like the kickstart course.